Innovations in weed management in rice - Singh, V. P.; Singh, S. P.; Sirazuddin, Sirazuddin; Tripathi, Neeta (Indian Farming, 2018)
Conventional herbicidal weed management strategy has occupied an important place both in direct seeded rice and transplanted rice, this approach has also brought many challenges and production vulnerabilities in crop production systems in general and rice ecologies in particular. These challenges included high cropd production costs due to escalating herbicide prices, rising environmental pollution, deterioration in food quality and soil- health due to herbicidal residues, and emerging risk of herbicide resistance in weeds. Thus, under aforesaid circumstances, there is a dire need to evolve and adopt potential alternative ecological approaches like enhanced competitiveness of rice through use of weed-competitive cultivars, increased seed rates, narrowed row spacing and allelopathy, all of which are greatly important, viable, and sustainable strategies to suppress the weeds at large.